2016
DOI: 10.1016/j.exer.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Human organotypic retinal cultures (HORCs) as a chronic experimental model for investigation of retinal ganglion cell degeneration

Abstract: There is a growing need for models of human diseases that utilise native, donated human tissue in order to model disease processes and develop novel therapeutic strategies. In this paper we assessed the suitability of aged human retinal explants as a potential model of chronic retinal ganglion cell (RGC) degeneration. Our results confirmed that RGC markers commonly used in rodent studies (NeuN, βIII Tubulin and Thy-1) were appropriate for labelling human RGCs and followed the expected differential expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 39 publications
0
46
0
5
Order By: Relevance
“…A later study by Niyadurupola et al focussed on the distribution and expression of thy1 under different neurotoxic stress conditions in adults . In an extension to this study, the distribution of RGCs using different markers were assessed and the utility of post‐mortem human retinal explants for long‐term study of RGCs was demonstrated …”
Section: Successful Applications Of Human Retinal Explants In Culturementioning
confidence: 87%
See 3 more Smart Citations
“…A later study by Niyadurupola et al focussed on the distribution and expression of thy1 under different neurotoxic stress conditions in adults . In an extension to this study, the distribution of RGCs using different markers were assessed and the utility of post‐mortem human retinal explants for long‐term study of RGCs was demonstrated …”
Section: Successful Applications Of Human Retinal Explants In Culturementioning
confidence: 87%
“…More recently, adult human retinal explants have been used for the study of human retinal ganglion cells (RGCs), photoreceptors and glial cells . Other retinal neurons like the amacrine cells, horizontal cells and bipolar cells have not been studied extensively either due to difficulties in culture or due to a perceived subordinate role in retinal pathology.…”
Section: History Of Human Retinal Explant Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The opportunity to investigate whole tissue cultures poses clear advantages compared to a monolayer of cultured cells, allowing the study of cell-to-cell interactions and maintaining an anatomical structure under EHP [28] . Exposure of retinal tissue obtained from human postmortem donors to EHP may also prove to be a useful model for testing the effectiveness of neuroprotective strategies [29,30] . Additionally, the use of EHP systems also promotes the reduction of animal use and the experimental variability intrinsic to animal models of glaucoma ( table 1 ).…”
Section: Advantages Of Using In Vitro Models To Study Glaucomamentioning
confidence: 99%